FINANCIAL PLANNING IN THE PADEMIC PERIOD - Franita, Riska (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2020)
The Covid 19 pandemic resulted in a new normal era that the Indonesian people must face. The unstable economic situation, the large number of unemployment and increasing poverty make the government have to be able to make the best decisions for its people. In financial management, financial planning is able to reduce poverty. Providing material and knowledge about good financial management can help the community in facing the new normal order. This research is a descriptive study, which examines financial planning in the new normal era. This study used online interview techniques and literature and literature reviews on financial planning in the new normal era. From the results of this study there are several things that must be considered such as a), regulating expenditure items, b) creating a budget, c) evaluating the amount of income d), looking for additional income e) delaying long-term investment f) closing non-important expenditure items g) avoid debt